2015
DOI: 10.2166/hydro.2015.113
|View full text |Cite
|
Sign up to set email alerts
|

Detecting anomalies in water distribution networks using EPR modelling paradigm

Abstract: Sustainable management of water distribution networks (WDNs) requires effective exploitation of available data from pressure and flow devices. Nowadays, water companies are collecting a large amount of such data and they need to be managed correctly and analysed effectively using appropriate techniques. Furthermore, water companies need to balance the data gathering and handling costs with the benefits of extracting information useful for making reliable operational decisions. Among different approaches develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(10 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Datadriven approaches focus on mining the burst-induced features from vast historical data, and then the leakage detection problem can be turned into a classification or clustering problem [19,20]. Laucelli et al investigated the effectiveness of the evolutionary polynomial regression paradigm to reproduce the behavior of a WDN using online data recorded by low-cost pressure/flow devices [21]. Palau et al applied principle component analysis (PCA) to the control of water inflows into DMAs of urban networks [22].…”
Section: Introductionmentioning
confidence: 99%
“…Datadriven approaches focus on mining the burst-induced features from vast historical data, and then the leakage detection problem can be turned into a classification or clustering problem [19,20]. Laucelli et al investigated the effectiveness of the evolutionary polynomial regression paradigm to reproduce the behavior of a WDN using online data recorded by low-cost pressure/flow devices [21]. Palau et al applied principle component analysis (PCA) to the control of water inflows into DMAs of urban networks [22].…”
Section: Introductionmentioning
confidence: 99%
“…The study revealed that the LSTM model effectively handles the shortcomings of ordinary artificial neural networks when predicting complex conditions in Smart Water Networks. In their work, Muharemi et al (2018) presented some approaches for abnormal event detection on aquatic time series data. Wang et al (2019) found that a deep learning method based on neural networks outperforms the support vector machine (SVM).…”
Section: Introductionmentioning
confidence: 99%
“…For example, around 7.85 × 10 9 m 3 of water was lost in 2017 in China (MOHURD, 2017). In addition, frequent pipe bursts may threaten public health (Fox et al, 2016), damage the urban environment (Laucelli et al, 2016), and disrupt the normal water supply service. Efficient and reliable detection of bursts helps water companies to react more quickly, saving scarce water resources, helping safeguard public health, and improve the sustainability of water supplies.…”
Section: Introductionmentioning
confidence: 99%